Does co-financing by multilateral development banks increase "risky" direct investment in emerging markets? - Torsten Wezel (Deutsche Bundesbank, 2004)
The paper discusses the question of whether financial participation of multilateral development banks does prompt private investors to inject more risky equity capital in emerging market banks. Using a theoretical model, it is stipulated that the presence of an official lender in a project gives the recipient country a stronger economic incentive to honor its contractual obligations instead of possibly restricting access to the investment position. An innovative endogenous variable measuring the amount of invested equity capital which, given a country's historical risk profile, can be considered "at risk" is tested in the empirical investigation. The observed outcome for the group of investors receiving co-financing by the International Finance Corporation (IFC) and/or the European Bank for Reconstruction and Development (EBRD) is related - applying a propensity score matching approach using information on the characteristics of non-participants - to the amount these firms would have invested had they not been selected for official support. The econometric results show that the "treatment effect" is significantly positive as stipulated. That is, in the German case financial participation of multilateral agencies in investment projects did have a positive impact on the risk exposure that investors were willing to bear.
Keywords: C14; G21; F21; 330; foreign direct investment; banks; emerging markets; multilateral development banks; program evaluation; propensity score matching; Direktinvestition; Deutsch; Internationale Kreditvergabe; Entwicklungsfinanzierung; Bankrisiko; Länderrisiko; Aufstrebende Märkte; Schätzung; Schwellenländer; Deutschland